Instructional Alignment in the Curriculum to Address Learner Diversity: The Case of High Schools in Egypt - Elshiekh, Shrouk (AUC Knowledge Fountain, 2023)
This research aims at exploring the connection between the instructional activities used by high school teachers to support diverse students, and the students’ readiness for college. This is accomplished by considering teachers’ awareness of their students' strengths and weaknesses and teachers’ collaboration with college counsellors. Both from the review of the literature and based on my experience as a high school teacher and college counsellor, it has emerged the necessity of addressing the diverse high school learners' needs through the application of the Universal Design for Learning (UDL) principles. The preparation of students for college through a precise alignment of the instructional activities with the learning outcomes has been identified as the most important step to be taken. The research findings highlight the importance of the role of a college counselling department, regular curriculum and syllabus reviews, as well as the introduction of ad-hoc instructional strategies and techniques. In particular, the findings and the related discussion can be helpful for educators and high school administrators when choosing the effective instructional strategies and techniques to meet the needs of diverse students in high schools. The findings of this study on students' opinions of college counsellors, especially on how they assisted them in selecting a college, can encourage institutions to reevaluate their current college counselling program.